Strategi Pengembangan Pasar Produk Coffee Drip Bag Asia Coffee melalui Sistem Pemasaran Digital Media Sosial Instagram - Mochamad Fauzan Ghagana Putra; Estri Mahani, Septiana Ayu; Saraswati , Nindya (Bandung Conference Series: Business and Management, 2024)
Abstract. The final report of this business project focuses on the product market development strategy through the Instagram social media digital marketing system for Asia Coffee, a trademark name since 2023 engaged in the beverage business. A competition and problems will definitely occur in running a business. Asia Coffee uses several analysis methods such as using SWOT analysis, five forces porter, balanced scorecard, SMART analysis, and boston consulting group matrix to determine the problems that occur. In addition, the analysis method also Asia Coffee gets a solution in solving its problems with product market development through the Instagram social media digital marketing system. In this final business report, Asia Coffee has written several developments in its business since its inception such as business legality registration to business activities that have been carried out. Thus, this strategy contributes significantly to the development of the Asia Coffee market to achieve sustainable growth and increase competitiveness in the market. Abstrak. Laporan akhir proyek bisnis ini berfokus pada strategi pengembangan pasar produk melalui sistem pemasaran digital media sosial instagram untuk Asia Coffee, merupakan sebuah nama merek dagang sejak tahun 2023 yang bergerak pada bisnis dibidang minuman. Sebuah persaingan dan permasalahan pasti akan terjadi dalam menjalankan sebuah bisnis. Asia Coffee menggunakan beberapa metode analisis seperti menggunakan SWOT analysis, five forces porter, balanced scorecard, SMART analysis, dan boston consulting group matrix untuk mengetahui permasalahan yang terjadi. Selain itu pada metode analisis tersebut juga Asia Coffee mendapatkan solusi dalam memecahkan permasalahannya dengan pengembangan pasar produk melalui sistem pemasaran digital media sosial instagram. Pada laporan akhir bisnis ini juga, Asia Coffee telah menuliskan beberapa perkembangan dalam usahanya sejak awal didirikan seperti pendaftaran legalitas usaha hingga aktivitas-aktivitas bisnis yang telah dilaksanakan. Dengan demikian, strategi ini memberikan kontribusi signifikan terhadap pengembangan pasar Asia Coffee untuk mencapai pertumbuhan yang berkelanjutan dan meningkatkan daya saing di pasar.